Driving Customer Satisfaction in the Digital Era: The Role of Service Experience and Payment Innovation at Jco Donuts & Coffee Thamrin Plaza: Mendorong Kepuasan Konsumen di Era Digital: Peran Pengalaman Layanan dan Inovasi Pembayaran di Jco Donuts & Coffee Thamrin Plaza - Salsa Salsa; Hommy Dorthy Elllyany Sinaga (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This study aims to examine the influence of customer experience and paymentinnovation on customer satisfaction at J.CO Donuts & Coffee Thamrin Plaza Medan. Theresearch method uses a quantitative approach and incidental sampling technique,involving 100 respondents who have made transactions through the J.CO digitalapplication. The data collection instrument is a questionnaire containing a Likert scale tomeasure the variables of customer experience (X₁), payment innovation (X₂), andcustomer satisfaction (Y). Data analysis was conducted through multiple linearregression with t-test and F-test. The results showed that customer experience variablehas a positive and significant effect on consumer satisfaction and payment innovationalso has a significant positive effect. Simultaneously, both variables can to explain 58.4%of the variation in consumer satisfaction. This also shows how important the ease ofapplication navigation, speed of order processing, staff professionalism, as well astransparency of terms and smooth cashback disbursement are to increase consumersatisfaction and create a better customer experience. Suggestions for J.CO Donuts &Coffee management include striving to be better in providing various paymentinnovations both through the application and website to reach a wider range of buyers.